Re-assessment of schistosomiasis in nine endemic districts with cluster sampling in Sierra Leone - Kargbo-Labour, Ibrahim; Redwood-Sawyerr, Victoria; Conteh, Abdulai; Chop, Elisabeth; Bah, Mohamed S.; Koroma, Abdulai; Kabia, Unidiatu; Klein, Luke; Juneja, Sugandh; Houck, Patricia; Reid, Steven; Evans, Darin; et al. (Frontiers in Public Health, 2024)
Background: Baseline mapping showed schistosomiasis was highly/moderately endemic in nine districts in Sierra Leone. Mass drug administration (MDA) with praziquantel started in 2009 and after multiple rounds of treatment, an impact assessment was conducted in 2016 followed by a second re-assessment in 2022 using cluster sampling to provide more granular data for refining chiefdom (sub-district) treatment strategies.Methods: An average of 20 rural villages were systematically selected per district by probability proportional to population size across the nine districts. Surveys were conducted in schools and 24 school children aged between 5 -14 years were randomly selected, with equal numbers of boys and girls. One stool and one urine sample were collected per child. Two Kato-Katz slides were examined per stool for Schistosoma mansoni infection. Haemastix strips were used as a proxy for S. haematobium infection with urine filtration used for egg counts on haematuria positive samples.Results: In total, across 200 schools in 125 chiefdoms, 4,736 stool samples and 4,618 urine samples were examined. Overall prevalence of S. mansoni was 16.3% (95% CI: 15.3-17.4%), while overall prevalence of S. haematobium was 2.0% (95% CI: 1.6-2.4) by haematuria.Prevalence of heavy infections for S. mansoni and S. haematobium was 1.5% (95% CI: 1.1-1.9) and 0.02% (95% CI: 0.0-0.14), respectively. Among 125 chiefdoms surveyed, overall schistosomiasis prevalence was <10% in 65 chiefdoms, 10 -49.9% in 47 chiefdoms and ≥50% Field Code Changed in 13 chiefdoms. There was mixed relationship between schistosomiasis in school children and WASH access in schools.Sierra Leone has made significant progress in reducing schistosomiasis prevalence across the country after a decade of MDA intervention. However, high prevalence remains in some hotspot chiefdoms. The next steps are for the national program to investigate and address any potential programmatic issues such as low coverage or poor knowledge of schistosomiasis risk behavior and where appropriate consider broadening to community-wide treatment in hotspot chiefdoms or communities.